Improvement of manganese phytoremediation by Broussonetia papyrifera with two plant growth promoting (PGP) Bacillus species. (December 2020) - Huang, Huimin; Zhao, Yunlin; Fan, Li; Jin, Qi; Yang, Guiyan; Xu, Zhenggang
Abstract: Combining phytoremediation plants and microorganisms is a promising method of remediating heavy metal contaminated soil. In this study, two manganese-tolerant strains were isolated from Mn slag and identified as Bacillus cereus HM5 and Bacillus thuringiensis HM7. These two Bacillus spp. have the ability to dissolve phosphorus, produce IAA and iron carrier. A pot experiment of Broussonetia papyrifera was conducted to explore potential of B. cereus HM5 and B. thuringiensis HM7 to improve effect of remedying Mn pollution by B. papyrifera . The strains were inoculated under different Mn treated (5 mmol/L, 50 mmol/L, Mn slag) respectively and the growth, root structure, root activity, physiological and biochemical characteristics of the leaves and accumulation of Mn for B. papyrifera were determinated. The effects of the soil environment to remediation were observed, the results showed that the biomass, total root length, surface area, crossings, tips, forks and root activity of B. papyrifera with inoculated strain were higher than those of the control group. The inoculation of these two Bacillus spp. increased the absorption of Mn by B. papyrifera and the concentration of Mn in the aerial parts of plants, indicating that the two strains could promote the growth of B. papyrifera and the accumulation of Mn. In addition, microbes reduced malonaldehyde content and the activities of antioxidant enzymes in leaves, suggesting that the two Bacillus spp. reduced Mn-induced oxidative stress. The principal component analysis showed that the added Bacillus strain prefer to promote plant root function maintenance and improve soil environment, rather than direct adsorption of heavy metals. These observations indicated that B. cereus HM5 and B. thuringiensis HM7 were valuable microorganisms, which could improve the remediating efficiency of B. papyrifera under Mn-contaminated soil. Highlights: B. cereus HM5/ B. thuringiensis HM7 improved the accumulation of Mn by B. papyrifera. B. cereus HM5 and B. thuringiensis HM7 could reduce oxidative stress induced by Mn. The strains promoted the growth of plant root system and improved soil environment.